Effects of a Groin Pain Prevention Program in Male High School Soccer Players: A Cluster-Randomized Controlled Trial - Kazuki Fujisaki; Kiyokazu Akasaka; Takahiro Otsudo; Hiroshi Hattori; Yuki Hasebe; Toby Hall (International Journal of Sports Physical Therapy)
# Background